Bulgarian Architectural Modernism, German Influences, and Industrial Architecture - Makarinov, Vassil; Karakolev, Theodore (Sledva : NBU Journal of Humanities and Arts, 2020)
Celebrating the 100th anniversary of Bauhaus school, a team of researchers from â€œBulgarian Modernist Architectureâ€ examined archives of German technical universities where Bulgarian architects studied in the first half of the 20th century. The archives in Munich, Berlin and Dresden have preserved the names and records of hundreds of Bulgarian architects from the 1910s, 1920s and 1930s. Their education, university professors, the environment in which they were formed (exhibitions, artistic trends and events) including Bauhaus connections, and how all of these informed the architecture in our country between the two world wars were among the questions explored by the researchers Vassil Makarinov and Theodore Karakolev. After the research in Germany, the team also plans to delve in the industrial architecture from the interwar period - a topic that is poorly known in our country.